PENGEMBANGAN MODEL PEMBELAJARAN FISIKA SMA BERBASIS GRAPHIC ORGANIZERS MELALUI BELAJAR KOOPERATIF TIPE STAD - Masril, Masril (Universitas Negeri Padang, 2012)
This article is based on the research about to design instructional model base on Graphic Organizers as one of the alternative instructional model to increase the understanding of student to Physics concepts in SMA. Special purpose is yield valid have been study peripheral model passed validation process to broader sample. To reach this purpose steps done is: 1) identifies student problems in high school, 2) discussion with physics teachers in the form of workshop, 3) designs of instructional model, and 4) verification model to expert and physics teachers in high school, and 5) Revision model as according suggestion. 6) Determines school sample based on school level. From model test result at sample school is obtained by score postest better than pretest Based on result of validation of study model through expert, high school physics teachers, and student as sample, inferential that model who designed have been valid although still many suggestions that need to be paid attention. Key words : Graphic Organizers, diagnostic test, instructional model